(untitled) (Scottish Historical and Archaeological Internet Reports, 2009)
In general extant horizons appear to match closely with known areas of Roman and medieval settlement but have been damaged in places by the creation of modern roads and services. Priority should be given to ensuring that work within the roadways of historic burghs is rigorously controlled.